The most useful cranial ultrasound predictor of neurodevelopmental outcome at 2 years for preterm infants. Issue 4 (April 2020) - Hou, W.; Tang, P.H.; Agarwal, P.
Abstract : AIM: To determine the most important cranial ultrasound predictors of abnormality associated with neurodevelopmental outcome at 2 years of age in preterm infants. MATERIALS AND METHODS: A total of 343 preterm infants born between 2005 and 2010 and cared for in KK Women's and Children's Hospital, a tertiary paediatric hospital, with birth weight ≤1, 250 g were assessed in this retrospective study. Serial cranial ultrasound examinations were examined for intraventricular haemorrhage and cystic periventricular leukomalacia. Ventricular–brain ratio on term equivalent cranial ultrasound was measured. Neurodevelopmental outcome was assessed by the performance on Bayley Scales of Infant and Toddler Development, 3 rd edition (Bayley-III) at 2 years corrected age. Mental delay was defined as having a combined Bayley-III score (the average of cognitive and language scores) <80. RESULTS: The mean cognitive, language, and motor scores on Bayley-III in this cohort were 93±15, 83±18, and 92±15, respectively. Twenty-six percent of the preterm infants had mental delay and 4% had cerebral palsy. Ventricular–brain ratio >0.35 was the most significant factor associated with mental delay (odds ratio 5.28, 95% CI: 1.49–18.71, p =0.01). Other significant risk factors for mental delay were male gender, postnatal steroids, and necrotising enterocolitis, whereas maternal tertiary education was a protective factor against adverse outcome. CONCLUSION: Ventricular–brain ratio >0.35 on term-equivalent cranial ultrasound in preterm infants is the strongest predictor for mental delay on Bayley score at 2 years of age. Highlights: Ventricular-brain ratio can be easily obtained from a coronal image at the level of the 3rd ventricle. Ventricular-brain ratio >0.35 is associated with lower cognitive, language and motor scores. Ventricular-brain ratio is the ultrasound parameter with the highest correlation with mental delay at 2 years.